2005
DOI: 10.1159/000082572
|View full text |Cite
|
Sign up to set email alerts
|

The Mystical Effects of Dermatological Vehicles

Abstract: Topical treatment of the skin is as old as the evolution of man. Instinctively, we try to treat a skin injury or irritation with cooling or soothing substances. Even animals lick their wounds, trusting instinctively in the healing power of saliva. When did this archaic pattern of treatment take the gigantic leap from folk medicine to modern drug therapy? This text illustrates the evolution of topical dermatological vehicles, their application (guidelines) and future use. In particular, a phenomenon that has so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 92 publications
0
53
0
7
Order By: Relevance
“…It is well known that skin penetration of drugs differs with different vehicles. 15,16) Activity in water is higher than that in LP because UF is freely soluble in LP but insoluble in water. 17) UF amount in the epidermis of stripped skin after application with water was significantly 10 times higher than that in LP.…”
Section: Penetration Of Uf Into Damaged Skinmentioning
confidence: 99%
“…It is well known that skin penetration of drugs differs with different vehicles. 15,16) Activity in water is higher than that in LP because UF is freely soluble in LP but insoluble in water. 17) UF amount in the epidermis of stripped skin after application with water was significantly 10 times higher than that in LP.…”
Section: Penetration Of Uf Into Damaged Skinmentioning
confidence: 99%
“…или ви-зуальных характеристик (краситель, молочко, пена, болтушка и т.д.) [6]. Традиционная классификация учитывает текстуру средства (твердая, полутвердая и жидкая) и физико-химическую структуру (однофаз-ная, 2-фазная и 3-фазная).…”
Section: -нарушения микробной колонизации (доми-нирование Staphylococunclassified
“…Up until the end of the 19 th century, the skin was widely regarded as being an impermeable barrier, even to the penetration of gases [2]. However, in 1893 Bourget and collaborators demonstrated that acute rheumatoid arthritis could be treated with topical salicylic acid [3]. In the early twentieth century it was recognised that more lipophilic agents had increased skin permeability [4].…”
Section: Introductionmentioning
confidence: 99%
“…During World War II, angina attacks were observed to be less frequent amongst munitions employees working with nitroglycerin [10]. Subsequently, in 1954, nitroglycerin ointment was introduced for the management of angina [3]. This was the first commercial topical preparation specifically developed to treat a systemic disease.…”
Section: Introductionmentioning
confidence: 99%